Study of the Mn2+ ions influence in the deposition electrolyte on the electrochromic properties of obtained Ni(OH)2 films - Kotok, Valerii; Kovalenko, Vadym (Eastern-European Journal of Enterprise Technologies, 2020)
An attempt was made to co-deposit nickel and manganese hydroxide films to be used as anodic electrochrome. Cathodic template method with polyvinyl alcohol was used for this. Deposition was conducted in the galvanostatic regime from the solution containing nickel and manganese nitrates in an 8:1 molar ratio. As a result of the work, two films were deposited: one from pure nickel nitrate and one from nickel and manganese nitrate solutions. Analysis of the synthesized films, revealed significant differences in structural, electrochemical and optical properties. The film deposited from the pure nickel nitrate solution was composed of a single α-like form Ni(OH)2. On the other hand, the film deposited from the manganese-containing solution was composed of two phases. Morphology comparison revealed that the surface of the undoped film is rather flat, with small bumps up to 160 nm. The Mn-doped film had many ridges of up to 1200 nm. Electrochemical properties of the film deposited in the presence of Mn were inferior to the film deposited from the pure solution. This is manifested in lower current densities and lower specific capacities of oxidation and reduction processes. Electrochromic properties of the film deposited in the presence of manganese were somewhat worse as well. A mechanism explaining the decrease of specific characteristics of the film in the case of using such deposition method was suggested. The mechanism lies in the formation of the second manganese-containing phase. This phase is rather inert and decreases the content of electrochemically active Ni(OH)2 in the film. The authors also suggested possible uses of the resulting structure